Stability of Fluorosurfactant Adsorption on Mineral Surface for Water Removal in Tight Gas Reservoirs - Lijun You; Wanchun Zhang; Yili Kang; Zhangxin Chen; Xuefen Liu (Journal of Chemistry)
Long-term effectiveness of rock wettability alteration for water removal during gas production from tight reservoir depends on the surfactant adsorption on the pore surface of a reservoir. This paper selected typical cationic fluorosurfactant FW-134 as an example and took advantage of Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), and atomic force microscope (AFM) to investigate its adsorption stability on the rock mineral surface under the oscillation condition at high temperature for a long time. The experimental results indicate that the F element content on the sample surface increases obviously, the surface structure of fluorine-carbonization also undergoes a significant change, and the fluorine surfactant exhibits a good interfacial modification and wettability alteration ability due to its adsorption on the pore surface transforming the chemical structure of the original surface. The adsorption increases indistinctly with the concentration of over 0.05% due to a single layer adsorption structure and is mainly electrostatic adsorption because the chemical bonding between the fluorosurfactant and the rock mineral surface, the hydrogen bonding, is weak and inconspicuous.